Aptamers: Novel Molecules as Diagnostic Markers in Bacterial and Viral Infections?. (5th September 2013) - Zimbres, Flávia M.; Tárnok, Attila; Ulrich, Henning; Wrenger, Carsten
Abstract : Worldwide the entire human population is at risk of infectious diseases of which a high degree is caused by pathogenic protozoans, worms, bacteria, and virus infections. Moreover the current medications against pathogenic agents are losing their efficacy due to increasing and even further spreading drug resistance. Therefore, there is an urgent need to discover novel diagnostic as well as therapeutic tools against infectious agents. In view of that, the Systematic Evolution of Ligands by Exponential Enrichment (SELEX) represents a powerful technology to target selectively pathogenic factors as well as entire bacteria or viruses. SELEX uses a large combinatorial oligonucleic acid library (DNA or RNA) which is processed a by high-flux in vitro screen of iterative cycles. The selected ligands, termed aptamers, are characterized by high specificity and affinity to their target molecule, which are already exploited in diagnostic and therapeutic applications. In this minireview we will discuss the current status of the SELEX technique applied on bacterial and viral pathogens.